PEMCRC anaphylaxis study protocol: a multicentre cohort study to derive and validate clinical decision models for the emergency department management of children with anaphylaxis. Issue 1 (5th January 2021) - Dribin, Timothy E; Michelson, Kenneth A; Vyles, David; Neuman, Mark I; Brousseau, David C; Mistry, Rakesh D; Dayan, Peter S; Zhang, Nanhua; Viswanathan, Shiv; Witry, John; Boyd, Stephanie; Schnadower, David
Abstract : Introduction: There remain significant knowledge gaps about the management and outcomes of children with anaphylaxis. These gaps have led to practice variation regarding decisions to hospitalise children and length of observation periods following treatment with epinephrine. The objectives of this multicentre study are to (1) determine the prevalence of and risk factors for severe, persistent, refractory and biphasic anaphylaxis, as well as persistent and biphasic non-anaphylactic reactions; (2) derive and validate prediction models for emergency department (ED) discharge; and (3) determine data-driven lengths of ED and inpatient observation prior to discharge to home based on initial reaction severity. Methods and analysis: The study is being conducted through the Pediatric Emergency Medicine Collaborative Research Committee (PEMCRC). Children 6 months to less than 18 years of age presenting to 30 participating EDs for anaphylaxis from October 2015 to December 2019 will be eligible. The primary outcomes for each objective are (1) severe, persistent, refractory or biphasic anaphylaxis, as well as persistent or biphasic non-anaphylactic reactions; (2) safe ED discharge, defined as no receipt of acute anaphylaxis medications or hypotension beyond 4 hours from first administered dose of epinephrine; and (3) time from first to last administered dose of epinephrine and vasopressor cessation. Analyses for each objective include (1) descriptive statistics to estimate prevalence and generalised estimating equations that will be used to investigate risk factors for anaphylaxis outcomes, (2) least absolute shrinkage and selection operator regression and binary recursive partitioning to derive and validate prediction models of children who may be candidates for safe ED discharge, and (3) Kaplan-Meier analyses to assess timing from first to last epinephrine doses and vasopressor cessation based on initial reaction severity. Ethics and dissemination: All sites will obtain institutional review board approval; results will be published in peer-reviewed journals and disseminated via traditional and social media, blogs and online education platforms.